2018
DOI: 10.5232/ricyde2018.05407
|View full text |Cite
|
Sign up to set email alerts
|

Open Journal Systems SCImago Journal & Country Rank Idioma/Language Ayuda de la revista Herramientas del artículo Imprimir este artículo Metadatos de indexación Cómo citar un elemento Referencias de búsqueda Enviar este artículo por correo electrónico Contenido de la revista Buscar Examinar Por número Por autor/a Por título Usuario/a Ha iniciado sesión como admin Mis revistas Mi perfil Cerrar sesión Elementos relacionados Mostrar todos Inicio/home Acerca de../Abo

Abstract: This study identified the game-related statistics that best differentiate national and foreign players competing in the 2014/15 and 2015/16 Portuguese Basketball League (LPB) seasons. Sample included 337 male professional basketball players, divided in national (n=249), community (n=30) and extra-community (n=58) according to their nationality. The following seventeen game-related statistics were obtained from the official box-scores of the Portuguese Basketball Federation: minutes, points scored, 2-point shot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
2
0
3
Order By: Relevance
“…However, comparative studies between native and foreign players have rarely employed similar approaches. Most studies have consistently demonstrated the superior capabilities of foreign players compared to native players, suggesting their need for a more significant on-court role (Guimarãe et al, 2018;Gasperi et al, 2020). Performance modeling helps mitigate these biases and preconceptions, enabling a fair and data-driven assessment of players from different backgrounds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, comparative studies between native and foreign players have rarely employed similar approaches. Most studies have consistently demonstrated the superior capabilities of foreign players compared to native players, suggesting their need for a more significant on-court role (Guimarãe et al, 2018;Gasperi et al, 2020). Performance modeling helps mitigate these biases and preconceptions, enabling a fair and data-driven assessment of players from different backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…Also, it was mentioned in their study that big players are generally unfavorable to the outcome of the game (Lutz, 2012), which diverges from our findings. Our explanation is that similar to the roles of native and foreign players in other leagues, native players play a secondary role in their team's offense, relying on their teammates to create chances while focusing more on defense and other secondary responsibilities and playing a lesser role in the creative aspects of the game (Guimarãe et al, 2018;Özmen, 2019); while some studies have also pointed out that big players who focus on defense have a positive impact on the outcome of the game (Lutz, 2012;Wang et al, 2022), which support our research findings. These insights prompt coaches to recognize that with all teams having the funds to recruit talented foreign players, it is vital to develop native players, especially big men with a great sense of teamwork and defensive ability.…”
Section: Discussionmentioning
confidence: 99%
“…Por otra parte, comparando a los jugadores extranjeros y nacionales en las dos temporadas, se observaron mejores valores en aspectos como el tiro exterior, las pérdidas, las tapas y las faltas personales en jugadores nacionales. Estas variables están relacionadas a la creación de juego en ofensiva y son similares a los resultados de Guimarães et al 26 donde observaron que los nacionales lideraron también en las estadísticas relacionadas a la creación de situaciones para el tiro y la anotación de compañeros (lo que definen como asistencias). Esto podría estar indicando que el rol principal de los jugadores nacionales es de armadores del ataque.…”
Section: Discussionunclassified
“…En relación al tiro a distancia, los resultados observados en la LUB fueron similares a los obtenidos en la LPB 26 . En ambos, los jugadores nacionales tiraron más de 3 puntos y tuvieron una mayor eficacia.…”
Section: Discussionunclassified
See 1 more Smart Citation